PENGARUH STRATEGI BISNIS,KEMAMPUAN MANAJERIAL PELAKU UMKM TERHADAP KINERJA UMKM PADA BIDANG KNALPOT DI KABUPATEN PURBALINGGA - Rahman, Alifa Aulia; Hirawati, Heni (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2022)
Purbalingga Regency has good potential in terms of its metal industry, one of the superior products with this metal base material is exhaust. This automotive component promises an opportunity in developing a business in the exhaust sector, so this research was conducted with the aim of testing the effect of business strategy and managerial capabilities of MSME actors on the performance of MSMEs in the exhaust sector in Purbalingga Regency. This study's sample was drawn from the population of MSME actors in the exhaust industry in Purbalingga Regency. Using the Slovin algorithm to determine the number of samples, 38 responders were gathered. The testing procedure employs multiple regression analysis. The findings of this study reveal that business strategy has no effect on the performance of MSMEs, however managerial skill has a substantial and significant effect on the performance of MSMEs in the exhaust sector in Purbalingga Regency. Simultaneously, the results shows that business strategy and managerial ability have a significant effect on the performance of MSMEs in MSMEs in the exhaust sector in Purbalingga Regency. The results of this study indicate that MSME actors in the exhaust sector have not implemented a business strategy in managing their business. Lack of work experience is a factor in the absence of a set strategy to help the process of running the business. On the other hand, MSME actors have good managerial skills.